Bilevel Programming and Applications. (1st March 2015) - Kalashnikov, Vyacheslav V.; Dempe, Stephan; Pérez-Valdés, Gerardo A.; Kalashnykova, Nataliya I.; Camacho-Vallejo, José-Fernando
Abstract : A great amount of new applied problems in the area of energy networks has recently arisen that can be efficiently solved only as mixed-integer bilevel programs. Among them are the natural gas cash-out problem, the deregulated electricity market equilibrium problem, biofuel problems, a problem of designing coupled energy carrier networks, and so forth, if we mention only part of such applications. Bilevel models to describe migration processes are also in the list of the most popular new themes of bilevel programming, as well as allocation, information protection, and cybersecurity problems. This survey provides a comprehensive review of some of the above-mentioned new areas including both theoretical and applied results.